An effective indicator determination for the leather material uniformity assessment - Danylkovych Аnatolii; Sanginova, Olga (Technology audit and production reserves, 2023)
The object of research is the process of determining the objective indicator of the degree of topographic homogeneity of the structure and properties of the leather material. The work defines a set of indicators of properties of semi-finished chrome tanning and leather materials. At the same time, when evaluating the homogeneity of the properties of leather materials, the difference between the values of the physical and mechanical indicators of the shabrack and the bottom is taken into account. At the same time, for a more homogeneous leather material, this difference should be minimal. The maximum differences between the determined physico-mechanical parameters of the semi-finished product of chrome tanning and the minimum for experimental and industrial leather materials were established. The given technological scheme for obtaining an experimental leather material by the technology of syntan-tannin filling-plasticization is more homogeneous with the use of syntan BNS TU 17-06-165-89, mimosa extract with a tannin content of 81.7 %, alkylcarboxyethanolamine of aliphatic acids, dye anionic black K, Fosfol L-1301 emulsions of Cromogenia Units, S.A. (Spain), aluminum potassium alum. For an objective assessment of the homogeneity of the properties of the leather material, a complex indicator is proposed – a coefficient that takes into account the meridian elongation at the crack of the face layer, the limit of strength of the material and its face layer at spherical deformation, which characterize the quality of the leather material according to DSTU 2726-94 «Leather for shoe uppers. Specifications». At the same time, the time-consuming nature of sample preparation and instrumental determination of the properties of leather material is taken into account. The determined complex coefficient of homogeneity of the experimental material is 0.88, and the industrial one is 0.82. This indicates greater homogeneity of the properties of the experimental leather material. A comprehensive analysis and evaluation of the homogeneity of the properties of the experimental leather material testify to the prospects of its use in the manufacture and operation of footwear products.